The Influence of Digital Literacy and Reading Interest on Students’ Critical Thinking Skills at SMAN 4 Bukittinggi - Herman Novia Rozi; Arif Arif (Darul Yasin Al Sys, 2026)
This study addresses the low level of students’ critical thinking skills in increasingly complex digital learning environments. It aims to examine the effects of digital literacy and reading interest on students’ critical thinking skills. A quantitative approach with a correlational research design was employed. The participants were students of SMAN 4 Bukittinggi, selected through proportional random sampling. Data were collected using validated questionnaires measuring digital literacy, reading interest, and critical thinking skills. The data were analyzed using descriptive statistics and multiple regression analysis, including the F-test and coefficient of determination. The findings reveal that digital literacy has a significant effect on students’ critical thinking skills (F = 79.405; p < 0.05), and reading interest also significantly influences students’ critical thinking skills (F = 3.244; p < 0.05). Furthermore, digital literacy and reading interest simultaneously have a significant effect on critical thinking skills (F = 64.425; p < 0.05). The Adjusted R Square value of 0.646 indicates that 64.6% of the variance in students’ critical thinking skills is explained by digital literacy and reading interest. These findings demonstrate that both digital literacy and reading interest play an important role in strengthening students’ higher-order thinking skills. The study contributes to educational practice by highlighting the need to integrate digital literacy development and reading-habit cultivation into learning activities to enhance students’ critical thinking skills in the digital era.